PUTUSAN VERSTEK KASUS PERCERAIAN SEBAB ADANYA PIHAK KETIGA DALAM RUMAH TANGGA BERDASARKAN PUTUSAN PENGADILAN NEGERI NOMOR 27/Pdt.G/2015/PN.Idm - Yamin, Syaefullah (Universitas Wiralodra, 2019)
A birth bond is the bond that can be seen and revealed the existence of legal relationship between a man and a woman to live together as husband and wife. In other words, it is called a formal relationship. This formal relationship is real in the binding matter and for the third party. A mental bond should be an informal relationship. It has to be a bond that is unseen, unreal, and only felt by an inner bond-the parties concerned. This inner bond is the basis of the birth bond. It could be used as a foundation in the building a happy family. Article 209 of BW decides that there are only 4 types of reasons which could be used as the basis for a marriage divorce. They are committing adultery with a third person (cheating), leaving the residence on purpose, receiving criminal punishment with imprisonment for 5 years or more after marriage, and injuring or persecuting by one party to another. It is feared that his death will be persecuted, or there are dangerous injuries existed. In this research, the researcher used the method of normative juridical approach. It is a study of the principles of law, legal systematics, level of law, synchronization of law, legal history, and comparative law. This research studies the case file writing No.27/pdt.G/2015?PN.Idm. While in terms of their nature, this research is a descriptive research. In this research, the researcher intends to obtain a juridical review of the verdict on divorce in case No.27/pdt.G/ 2016/PN.idm. The reason for filing a divorce application in case Number 27/Pdt.G/2015/PN.Idm is because between the plaintiff and the defendant as husband and wife, there are often quarrels existed. It makes the plaintiff and defendant's household not harmonious.